Damage control articular surgery: Maintaining chondrocyte health and minimising iatrogenic injury. (May 2020) - Howard, Thomas A.; Murray, Iain R.; Amin, Anish K.; Simpson, A. Hamish; Hall, Andrew C.
Highlights: No chondrocyte division occurs in adult cartilage, and articular cartilage is incapable of effective repair. Untreated lesions may progress to degenerative joint disease. Significant chondrocyte death can be caused iatrogentically by sharp or blunt instruments, drilling, or by exposing articular cartilage to laminar airflow. These insults can be exacerbated by hyposmolar and high calcium-containing irrigation fluids. Keeping the joint moist, cool and appropriately hydrated with a hyperosmolar, low calcium irrigation fluid are shown to be chondroprotective. Abstract: Articular cartilage has limited intrinsic regenerative potential. The maintenance of healthy articular cartilage is essential to prevent joint degeneration and the morbidity associated with arthritis. In this review, we outline the structure and function of healthy articular cartilage. We summarise some of the recent literature outlining the influence of surgical factors on chondrocyte health. These factors include mechanical injury from instrumentation and drilling, drying, and the influence of irrigation fluids, antimicrobial solutions and local anaesthetics. We demonstrate that there is scope for improving cartilage viability at the time of surgery if simple chondroprotective measures are routinely adopted.